2004
DOI: 10.1128/iai.72.10.5582-5596.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Pneumococcal Gene Expression during Invasive Disease

Abstract: Streptococcus pneumoniae is a leading cause of invasive bacterial disease. This is the first study to examine the expression of S. pneumoniae genes in vivo by using whole-genome microarrays available from The Institute for Genomic Research. Total RNA was collected from pneumococci isolated from infected blood, infected cerebrospinal fluid, and bacteria attached to a pharyngeal epithelial cell line in vitro. Microarray analysis of pneumococcal genes expressed in these models identified body site-specific patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
232
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(260 citation statements)
references
References 53 publications
23
232
2
3
Order By: Relevance
“…The invasiveness of serotype 4 clinical isolates could depend on a particular genotype, which is beneficial for invasiveness, rather than the capsular serotype per se. TIGR4 was originally isolated from meningitis, and although it is able to cause meningitis in mice, its yield in blood was low in contrast to serotype 2 D39, which attains high titers in blood after challenge (36). This could indicate that the invasiveness of the TIGR4 strain is not as high as it is for serotype 4 clinical isolates from invasive disease.…”
Section: Discussionmentioning
confidence: 91%
“…The invasiveness of serotype 4 clinical isolates could depend on a particular genotype, which is beneficial for invasiveness, rather than the capsular serotype per se. TIGR4 was originally isolated from meningitis, and although it is able to cause meningitis in mice, its yield in blood was low in contrast to serotype 2 D39, which attains high titers in blood after challenge (36). This could indicate that the invasiveness of the TIGR4 strain is not as high as it is for serotype 4 clinical isolates from invasive disease.…”
Section: Discussionmentioning
confidence: 91%
“…Pneumococcal infections commence at the nasopharynx, where the bacteria reside as commensals without harming the host niche. Colonization of the respiratory mucosal epithelium is a prerequisite for invasive infections, which are most likely accompanied by dramatic changes in the nasopharyngeal physical barriers and the expression of pneumococcal virulence factors (Orihuela et al, 2004). The repertoire of uptake systems for essential nutrients enables pneumococci to adapt to and survive in different physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Attachment of S. pneumoniae to respiratory epithelial cells is mediated by serum or extracellular matrix proteins including complement Factor H, thrombospondin-1 and vitronectin (Agarwal et al, 2010b;Bergmann et al, 2009;Hammerschmidt et al, 2007;Rennemeier et al, 2007). In addition, pneumococci produce surface proteins interacting directly with host cellular receptors such as the choline-binding protein PspC (pneumococcal surface protein C, also referred to as CbpA or SpsA), RrgA of Pilus-1, PavB and PsrP (Barocchi et al, 2006;Elm et al, 2004;Jensch et al, 2010;Orihuela et al, 2004;Zhang et al, 2000). Although the repertoire of virulence factors and adhesins differs among pneumococcal isolates, redundant virulence factors must be present in pneumococci as mutations in single genes can be compensated for by others (Bergmann & Hammerschmidt, 2006;Kadioglu et al, 2008;Nobbs et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that deletion of late genes, including lytA, cibAB , and cbpD , decreased pneumococcal virulence in mouse models of pneumonia and bacteremia, many of the genes in that study were hypothetical or conserved hypothetical proteins, and their roles in pneumococcal pathogenesis are unknown [25]. Previous comprehensive analysis findings showed that S. pneumoniae ccs4 expression is upregulated when the bacteria make contact with host cells, including pharyngeal epithelial [17] and alveolar epithelial [16] cells. Therefore, there is a possibility that Css4 is expressed by bacteria in contact with the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding candidate combox sites 4 (Ccs4) has been reported to be a late competence gene and ccs4 deletion had no effect on the transformation efficiency of S. pneumoniae [15]. However, previous comprehensive analysis findings revealed that the transcriptional activity of ccs4 was increased during co-incubation with lung and pharyngeal epithelial cells [16,17]. Additionally, using a mouse model of pneumonia and meningitis, real-time RT-PCR analysis showed increased expression of competence genes following infection of lung and brain tissues [14].…”
Section: Introductionmentioning
confidence: 99%